Development of articulate storyline media based on local wisdom of Meron Tradition for student engagement - Ayu Intan Safitri; Yuli Witanto (Research and Development in Education (RaDEn), 2025)
The learning outcomes of students in Mathematics, particularly on addition and subtraction of fraction, are hindered by the lack of innovative and engaging learning media tailored to students' needs. Consequently, learning becomes monotonous and less effective, resulting in decreased student motivation. This study aims to develop, test the feasibility, and examine the effectiveness of articulate storyline media based on the Local wisdom of the Meron Tradition in Pati in improving learning outcomes for fifth-grade students at SDN Blaru 02. Employing the Research and Development (R&D) method with the Borg & Gall model, this study utilized tests, questionnaires, observations, interviews, and documentation for data collection. The results indicated that the media's feasibility was rated 88.3% by media experts and 92.6% by material experts, categorized as "very feasible." The t-test results revealed a significant difference with a sig. (2-tailed) of 0.000 and t value of 9.983 (t-table = 2.051). The N-gain score of 0.609 indicated a moderate improvement in learning outcomes. These findings conclude that articulate storyline media based on the local wisdom of the Meron Tradition is valid, engaging, and effective in enhancing student learning outcomes.